2022
DOI: 10.18280/ijsse.120507
|View full text |Cite
|
Sign up to set email alerts
|

The Main Systemic Engineering Problems of Using Computer and Digital Technologies in Legal Activities in the Context of Ensuring Security

Abstract: The relevance of the research topic is accompanied by a great demand for digital and computer technologies and their rapid growth in the activities of any organization. Legal activity and security have changed a lot in recent years and also feels the impact of modern digital and computer technologies. The main purpose of the article is to study the main systemic engineering problems of using digital and computer technologies in the legal activities of firms in terms of ensuring security. To achieve this goal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Thus, some scientists concluded that the legal function of ensuring safety and security development is carried out by criminal law by establishing a range of socially dangerous acts recognized as crimes, as well as criminal penalties and other measures of criminal law enforcement applied to those who committed them. By thus protecting social relations, criminal law further regulates other social relations -arising between the state and a person who has committed a socially dangerous act in connection with bringing the latter to criminal responsibility [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some scientists concluded that the legal function of ensuring safety and security development is carried out by criminal law by establishing a range of socially dangerous acts recognized as crimes, as well as criminal penalties and other measures of criminal law enforcement applied to those who committed them. By thus protecting social relations, criminal law further regulates other social relations -arising between the state and a person who has committed a socially dangerous act in connection with bringing the latter to criminal responsibility [11,12].…”
Section: Discussionmentioning
confidence: 99%